2013
DOI: 10.1074/jbc.m113.461798
|View full text |Cite
|
Sign up to set email alerts
|

Folate Stress Induces Apoptosis via p53-dependent de Novo Ceramide Synthesis and Up-regulation of Ceramide Synthase 6

Abstract: Background: Sphingolipid ceramide regulates cellular responses to stress stimuli. Results: Aldh1l1, the enzyme regulating folate metabolism, leads to CerS6 up-regulation and C 16 -ceramide accumulation in a p53-dependent manner as a proapoptotic signal. Conclusion: Ceramide mediates the cellular response to nongenotoxic folate stress. Significance: We have demonstrated the interaction between two major metabolic pathways, folate and sphingolipids, in regulation of cellular homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 60 publications
1
56
0
Order By: Relevance
“…Thus, our previous study demonstrated that CerS6 is elevated in a p53-dependent manner in response to folate stress enzyme ALDH1L1 (28); ALDH1L1, however, induces p53 through metabolic alterations in the absence of DNA damage (33,58). In line with this finding, the treatment of cancer cells with antifolate methotrexate or folate withdrawal, two stimuli inducing alterations in folate, amino acid, and nucleotide metabolism, activated CerS6 in a p53-dependent fashion (28,31). In the present study the transcriptional induction of CerS6 by p53 in the absence of genotoxic stress was further confirmed using two canonical activators of p53, actinomycin D and Nutlin-3, which do not induce DNA damage.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Thus, our previous study demonstrated that CerS6 is elevated in a p53-dependent manner in response to folate stress enzyme ALDH1L1 (28); ALDH1L1, however, induces p53 through metabolic alterations in the absence of DNA damage (33,58). In line with this finding, the treatment of cancer cells with antifolate methotrexate or folate withdrawal, two stimuli inducing alterations in folate, amino acid, and nucleotide metabolism, activated CerS6 in a p53-dependent fashion (28,31). In the present study the transcriptional induction of CerS6 by p53 in the absence of genotoxic stress was further confirmed using two canonical activators of p53, actinomycin D and Nutlin-3, which do not induce DNA damage.…”
Section: Discussionsupporting
confidence: 69%
“…To eliminate potential impact from endogenous p53 protein on CerS6 promoter, we have also performed luciferase assays in the p53-deficient A549 cell line. In this cell line p53 was silenced by the stable expression of the p53 shRNA, which completely prevented the protein expression (28,33). Similar to p53-proficient A549 cells, strong activation of luciferase was seen in the p53-deficient cells upon co-expression with the p53-expressing vector but not the vector expressing mutant p53 (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Consequently, reduced expression of CerS2 has been shown to be a negative prognostic indicator in breast cancer patients (4). Similarly, CerS6 promotes therapy-induced apoptosis in colon cancer cells (5,6), head and neck squamous cell carcinoma, and lung carcinomas (7,8), and CerS1 acts as a proapoptotic factor in multiple cancer cell lines (9,10).…”
mentioning
confidence: 99%